Dana to directly distribute Victor Reinz gaskets in North America. Issue 9 (September 2016) - Unknown
Abstract : Dana Holding Corp, a US company that develops engineered driveline, sealing and thermal-management technologies, says that it will begin selling its original-equipment line of gaskets and sealing products, under the Victor Reinz brand name, directly to its network of aftermarket customers in North America – starting on 1 November 2016.